Gas Production from Methane Hydrate in a Pilot-Scale Hydrate Simulator Using the Huff and Puff Method by Experimental and Numerical Studies - Li, Bo; Li, Gang; Li, Xiao-Sen; Li, Qing-Ping; Yang, Bo; Zhang, Yu; Chen, Zhao-Yang (Energy & Fuels, 2012)
A novel three-dimensional 117.8-L pressure vessel, which is called a Pilot-Scale Hydrate Simulator (PHS), is developed to investigate the gas production performance from hydrate-bearing porous media using the huff and puff method through both experimental and numerical simulations. The methane gas and deionized water are injected into the pressure vessel to synthesize methane hydrate. The grain sizes of the quartz sand in the vessel are between 300 and 450 mu m. The huff and puff stages, including the injection, the soaking, and the production, are employed for hydrate dissociation. A single vertical well at the axis of the PHS is used as the injection and production well. The whole experiment consists of 15 huff and puff cycles. The numerical simulation results agree well with the experiment. Both the experimental and numerical simulation results indicate that the injected water is mainly restricted around the well during the injection stage. The system pressure fluctuates regularly in each cycle, and the secondary hydrate is formed under the pressurization effect caused by the hot water injection in the injection stage. The gas production rate maintains approximately stable in a relatively long period. The sensitivity analysis indicates that the gas production can be enhanced with high intrinsic permeability of the deposit or by raising the temperature of the injected hot water. The mass of the water produced in each cycle has little difference and is manageable when using the huff and puff method.